Efficiency of treatment and diagnostic algorithms in the rehabilitation program of women after hysterectomy with opportunist salpingectomy due to uterine myoma - O.M. Proshchenko; I.B. Ventskivska (Publishing House TRILIST, 2022)
Objectives: to determine the effectiveness of the rehabilitation program in women of reproductive age with uterine fibroids for correction of genitourinary syndrome after hysterectomy with opportunistic salpingectomy. Materials and methods. 160 women were examined after hysterectomy with fallopian tubes. State of the urogenital tract and urogenital dysfunction researched with the using the POP-Q system, the Barlow scale, vaginoscopy. Also it was used evaluation of the vaginal pH and mucosal microbiota state, assessment of the vaginal health index according to G. Bochmann, assessment of the impact of vulvovaginal symptoms on the life's quality with the MOS SF-36 questionnaire in the dynamics of the postoperative period. The treatment algorithm included local preparations of hyaluronic acid, lactobacillus preparations in combination with vitamin D solution, in case of a severe course - topical estrogens, in case of vasomotor symptoms - estradiol 50 μg/day and vitamin D 4000 IU daily or 20,000 IU once a week. Results. Manifestations of genitourinary syndrome were revealed 1 year after surgery, namely: hypotrophy of the vaginal mucous membrane in 36.3% of women, urinary incontinence in almost a third of patients, prolapse of the vaginal walls of the I-II degree in 8.8% of women, a pathological microscopic picture in 68.1% of female. The proposed algorithms in the rehabilitation program made it possible to eliminate or reduce the severity of genitourinary symptoms 5 years after hysterectomy, in particular, to reduce the frequency of vulvovaginal atrophy by 25%, to normalize the biocenosis and pH of the vaginal contents, to reduce the clinical manifestations of urination disorders (pollakiuria and nocturia by 14% and 12,8%, respectively), feeling of incomplete emptying of the bladder by 12.9%, stress urinary incontinence by 17.9%, vaginal prolapse by 13.3% compared to the group with standard postoperative management. Conclusions. Hysterectomy with opportunistic salpingectomy for uterine fibroids has a positive effect on the life's quality of patients by improving the physical comfort due to the reduction of clinical symptoms of uterine fibroids. However, changes in the quality of life after surgical intervention associated with disturbances in the psycho-emotional sphere were recorded in 49.4% of women, including those provoked by the manifestation of genitourinary syndrome in 19.3%. The proposed algorithm in the rehabilitation program made it possible to reduces the severity of genitourinary symptoms.